IMPROVEMENT OF THE FISCAL POLICY OF UKRAINE UNDER THE CONDITIONS OF THE FORMATION OF A DIGITAL ECONOMY (ІННОВАЦІЙНА ЕКОНОМІКА, 2022)
Данилків Х.П., Дропа Я.Б., Петик М.І., Гавран В.Я. УДОСКОНАЛЕННЯ ФІСКАЛЬНОЇ ПОЛІТИКИ УКРАЇНИ ЗА УМОВ ФОРМУВАННЯ ЦИФРОВОЇ ЕКОНОМІКИМета. Визначення напрямів удосконалення фіскальної політики держави в умовах діджиталізації фінансової системи та посилення євроінтеграційних процесів в Україні.Методика дослідження. Для досягнення визначеної мети використано комплекс сучасних наукових методів дослідження, зокрема: логічний – з метою поступової систематизації теоретичних і практичних засад дослідження; індукція і дедукція – для формулювання обґрунтованих висновків і пропозицій; аналіз і синтез – з метою виявлення чинників, що визначають фіскальну політику держави; статистичні методи (групування, порівняння, рядів динаміки) – для формування масиву даних та проведення аналізу ефективності фіскальної політики; табличний і графічний методи, структурний аналіз – для проведення аналізу структури і динаміки бюджетних доходів і видатків та визначення ефективності фіскальної політики.Результати дослідження. Розглянуто фіскальну політику з погляду комплексу фінансових дій уряду щодо забезпечення можливості фінансування визначеного розміру та співвідношення бюджетних видатків, організації оптимальної системи міжбюджетних відносин та створення ефективного механізму оподаткування суб’єктів господарювання та населення країни. Розкрито подвійну природу фіскальної політики, яка охоплює дві складові: податкову політику та політику здійснення бюджетних видатків. Наголошено на необхідності координації діяльності уряду у напрямі мобілізації податкових надходжень бюджетної системи та здійснення бюджетних видатків з метою забезпечення соціально-економічного розвитку національної економіки.Інструменти фіскальної політики висвітлено з погляду сукупності засобів, які застосовують у процесі вилучення частини грошових коштів у суб’єктів господарювання та населення з метою забезпечення мобілізації достатнього обсягу фінансових ресурсів у бюджетній системі країни. Фіскальний механізм подано у розрізі податкової та бюджетної складової, які взаємодіють між собою, допомагають перерозподіляти ВВП та володіють відповідними інструментами. Обґрунтовано його призначення – залучення достатніх обсягів фінансових ресурсів у бюджетну систему з метою виконання державою покладених на неї функцій і завдань.Аргументовано тісну кореляцію між обсягом мобілізованих податків та розміром здійснених бюджетних видатків. Підкреслено, що реалізація ефективної бюджетно-податкової політики здатна поліпшити інвестиційний клімат в країні та пришвидшити темпи економічного зростання. Проведено оцінку ефективності вітчизняної податкової політики за допомогою аналізу динаміки і структури податкових надходжень до бюджетної системи упродовж 2010-2021 років. Виявлено негативний вплив на розвиток економіки України таких чинників, які стали причиною виникнення багатьох конструктивних проблем: ведення військових дій на території країни, далека від оптимальної кон’юнктура національного ринку товарів і послуг, падіння доходів домогосподарств, розбалансованість економіки тощо.Визначено напрями удосконалення податкової політики в Україні в умовах посилення євроінтеграційних процесів, аргументовано необхідність впровадження програмно-цільового методу в управління бюджетними видатками.Проаналізовано динаміку та структуру видатків державного і місцевих бюджетів Україні за функціональною й економічною класифікацією, наголошено на необхідності удосконалення міжбюджетних відносин з метою нарощення фінансової бази місцевого самоврядування. Запропоновано напрями удосконалення вітчизняної бюджетної політики з метою перетворення її на інструмент забезпечення економічного розвитку країни.Окреслено головні проблеми реалізації та визначено способи поліпшення боргової політики держави з погляду її взаємозв’язку з податковою та видатковою складовою бюджетної системи. Головними напрямами удосконалення фіскальної політики держави визначено підвищення її прозорості за допомогою парцитипаторного бюджетування, впровадження системи електронних сервісів і застосування інноваційних цифрових технологій у державних фінансах.Наукова новизна результатів дослідження. Визначено негативні фіскальні чинники, що стримують розвиток національної економіки за допомогою аналізу структури та динаміки доходів і видатків бюджетної системи; запропоновано напрями удосконалення вітчизняної податкової політики та політки бюджетних видатків з метою стимулювання економічного зростання;  виявлено головні проблеми та обґрунтовано способи поліпшення боргової політики України в умовах євроінтеграції; аргументовано доцільність застосування сучасних цифрових технологій з метою удосконалення фіскальної політики України.Практична значущість результатів дослідження. Результати проведеного дослідження щодо формування та реалізації фіскальної політики в умовах експансії цифрових технологій допоможуть уряду України перетворити політику у сфері податків, бюджетних видатків і державного боргу у головний інструмент забезпечення розвитку країни в умовах посилення процесів євроінтеграції.Ключові слова: фіскальна політика, податки, бюджетні видатки, державний борг, партиципаторний бюджет, електронні сервіси, Prozorro, державні закупівлі, цифрова економіка. Danylkiv Kh.P., Dropa Ya.B., Petyk M.I., Havran V.Ya. IMPROVEMENT OF THE FISCAL POLICY OF UKRAINE UNDER THE CONDITIONS OF THE FORMATION OF A DIGITAL ECONOMYPurpose. The purpose of the scientific work is to determine directions for improving the state's fiscal policy in the context of digitalization of the financial system and strengthening of European integration processes in Ukraine.Methodology of research. To achieve the defined goal, a complex of modern scientific research methods was used, in particular: logical – to gradually systematize the theoretical and practical principles of research; induction and deduction – for formulating well-founded conclusions and proposals; analysis and synthesis – to identify the factors that determine the fiscal policy of the state; statistical methods (grouping, comparison, series of dynamics) – for forming a data array and conducting an analysis of the effectiveness of fiscal policy; tabular and graphical methods, structural analysis – for analyzing the structure and dynamics of budget revenues and expenditures and determining the effectiveness of the fiscal policy.Findings. The article examines the fiscal policy from the point of view of the complex of financial actions of the government to ensure the possibility of financing a certain amount and ratio of budget expenditures, the organization of an optimal system of inter-budgetary relations, and the creation of an effective mechanism for taxation of economic entities and the country's population. The dual nature of fiscal policy, which includes two components: tax policy and budget expenditure policy, is revealed. The need to coordinate the government's activities in the direction of mobilizing tax revenues of the budget system and implementing budget expenditures to ensure the social and economic development of the national economy is emphasized.Fiscal policy tools are highlighted from the point of view of the set of means used in the process of withdrawing part of the funds from business entities and the population to ensure the mobilization of a sufficient amount of financial resources in the country's budget system. The fiscal mechanism is presented in terms of tax and budget components, which interact with each other, help to redistribute GDP, and have the appropriate tools. Its purpose is well-founded - attracting sufficient amounts of financial resources into the budget system to fulfill the functions and tasks assigned to it by the state.A close correlation between the volume of mobilized taxes and the number of budget expenditures is argued. It is emphasized that the implementation of an effective budget and tax policy can improve the investment climate in the country and accelerates the rate of economic growth. The effectiveness of the domestic tax policy was assessed using the analysis of the dynamics and structure of tax revenues to the budget system during 2010-2021. The negative impact on the development of the economy of Ukraine was revealed by the following factors, which caused the emergence of many constructive problems: the conduct of military operations on the territory of the country, the far from the optimal situation of the national market of goods and services, the drop in household incomes, the imbalance of the economy, etc.The areas of improvement of the tax policy in Ukraine in the conditions of the strengthening of the European integration processes are defined, and the necessity of introducing a program-target method in the management of budget expenditures is argued.The dynamics and structure of expenditures of the state and local budgets of Ukraine according to functional and economic classification are analyzed, and the need to improve inter-budgetary relations to increase the financial base of local self-government is emphasized. Directions for improving the domestic budget policy to turn it into a tool for ensuring the country's economic development are proposed.The main problems of implementation are outlined and ways to improve the state's debt policy from the point of view of its relationship with the tax and expenditure component of the budget system are determined. The main areas of improvement of the fiscal policy of the state are determined to increase its transparency with the help of participatory budgeting, the introduction of a system of electronic services, and the use of innovative digital technologies in public finances.Originality. The negative fiscal factors restraining the development of the national economy were determined using an analysis of the structure and dynamics of revenues and expenditures of the budget system; directions for improving the domestic tax policy and the policy of budget expenditures to stimulate economic growth are proposed; the main problems are identified and the ways of improving the debt policy of Ukraine in the conditions of European integration are substantiated; the expediency of using modern digital technologies to improve the fiscal policy of Ukraine is argued.Practical value. The results of the conducted research on the formation and implementation of fiscal policy in the conditions of the expansion of digital technologies will help the government of Ukraine to transform the policy in the field of taxes, budget expenditures, and public debt into the main tool for ensuring the country's development in the conditions of strengthening the processes of European integration.Key words: fiscal policy, taxes, budget expenditures, public debt, participatory budget, electronic services, Prozoro, public procurement, digital economy.
Keywords: fiscal policy; taxes; budget expenditures; public debt; participatory budget; electronic services; Prozoro; public procurement; digital economy.